2018
DOI: 10.1002/polb.24603
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic polyurethanes with double decker silsesquioxanes in the main chains: Morphologies, surface hydrophobicity, and shape memory properties

Abstract: Ultrafast shock compression waves are launched from an Al ablation layer (grainy surface) driven by a nanosecond duration laser pulse through a 5-micron layer of polydimethylsiloxane (PDMS), coated by a thin layer of Al (squares). Shock transit time and wave profiles characterize the polymer response to very rapid compression. On page 827, Michael Armstrong and colleagues show that the high strain rate response of PDMS-based polymers is correlated with their static compressibility, and that these polymers exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
(48 reference statements)
0
25
1
Order By: Relevance
“…Besides, the strong hydrophobicity of POSS can possibly have an impact on the surficial properties of hydrogels by generating a POSS-enriched layer on the surface. The hydrophobic surface provides some interesting modifications, such as improved biocompatibility, reduced coefficient of friction and antifouling ability, profiting the utilization of hydrogels as biomaterials or water treatment materials …”
Section: Advantages and Challenges Of Poss-containing Hydrogelsmentioning
confidence: 99%
“…Besides, the strong hydrophobicity of POSS can possibly have an impact on the surficial properties of hydrogels by generating a POSS-enriched layer on the surface. The hydrophobic surface provides some interesting modifications, such as improved biocompatibility, reduced coefficient of friction and antifouling ability, profiting the utilization of hydrogels as biomaterials or water treatment materials …”
Section: Advantages and Challenges Of Poss-containing Hydrogelsmentioning
confidence: 99%
“…The hydrophobicity and mechanical performance of the liner PU with B-POSS was obviously enhanced as well. Xu et al [115] also investigated organic-inorganic polyurethanes with B-POSS, and found that the microphase separation of POSS was self-organized into spherical microdomains 10-50 nm in diameter. Raftopoulos et al [116] reported the molecular dynamics and morphology of a polyurethane system with POSS through SEM, DSC, (thermally stimulated depolarization currents) (TSDC), and DMA.…”
Section: Pu-possmentioning
confidence: 99%
“…8,9 For example, Liang introduced trimethoxysilane (3-[2-aminoethyl] aminopropyl) to synthesize a group of water-based polyurethanes containing alkoxy silane groups in side chains that had low-water absorption and high-thermal properties with an addition of 2.0% by weight. 10 While organic-inorganic hybrid modification usually incorporates different types of nanocomposites in WPU to enhance performance 11 , including silica 12 , cellulose nanocrystals, 13 graphene, 14 and polysiloxane, 15,16 and so on.…”
Section: Introductionmentioning
confidence: 99%